Aktywność czytelnicza w edukacji wczesnoszkolnej = The activity of reading in early education - Kochan, Katarzyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Early Education is an important time in the life of every person. It is the foundation for further education and is sometimes shaping the attitudes. At this time, when the child learns the code letters and acquire knowledge of reading and writing, there is also the socialization of reading.
Keywords: edukacja wczesnoszkolna; uczeń; czytanie; czytelnictwo; biblioterapia; early education; pupil; reading; bibliotherapy